2007
DOI: 10.1097/jom.0b013e31815ac4f8
|View full text |Cite
|
Sign up to set email alerts
|

The World Trade Center Clean Up and Recovery Worker Cohort Study: Respiratory Health Amongst Cleanup Workers Approximately 20 Months After Initial Exposure at the Disaster Site

Abstract: These results suggest an impact on respiratory health related to work experience at the WTC and indicate further monitoring to address potential long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Our response rates are similar to other WTC studies Tao et al 2007). In particular, our experience was similar to that described by Tao et al (2007), who also reported a low response rate that diVered by exposure groups.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our response rates are similar to other WTC studies Tao et al 2007). In particular, our experience was similar to that described by Tao et al (2007), who also reported a low response rate that diVered by exposure groups.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, our experience was similar to that described by Tao et al (2007), who also reported a low response rate that diVered by exposure groups. It is often believed that persons with health symptoms are more likely to respond to health surveys.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many studies have examined exposure to health hazards [6][7][8][9][10][11][12] and traumatic stress after disasters, 15-24 but few have analyzed disaster-related occupational health needs in workplaces. [25][26][27] This may be because companies are reluctant to disclose data even when various occupational health needs have arisen.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to health issues related to disasters, many studies have been conducted on the long-term health effects on emergency responders, [6][7][8][9][10][11][12] health effects on local residents after accidents at chemical plants, 13,14 and programs dealing with traumatic stress. [15][16][17][18][19][20][21][22][23][24] Except for studies by external occupational health experts examining the occupational health needs arising at workplaces during large-scale disasters, 25,26 few case reports on this matter have been published.…”
mentioning
confidence: 99%